Opportunities for University in the XXI century (Revista de Investigaciones Universidad del Quindío, 2010)
This research work reviews a growing literature that enquires about the future role of the University as a leading organization that helps to transform traditional knowledge into research practices useful to innovation. We explore in this review, how the traditional teaching practices followed by universities, has evolved, converting teaching institutions into research institutes that link with innovative needs demanded by multinational corporations. Social value added rises after research, development and innovation practices link together traditional knowledge with innovative practices followed by universities, research centers and firms. A new university mission develops as competences defined as skills, knowledge, and attributes are developed to spread innovation practices into the world competitive firm.
Keywords: International Business; Research Practices; Innovation; Competences; Supply Chain; Services; Competitiviness